Multi-specific coral spawning and monsoonal transitions: assemblage-level observations from Baa Atoll, Maldives - Errington, Amelia J. F.; Moody, Kate; Le Berre, Thomas (Frontiers in Marine Science, 2025)
Coral reefs support a vast diversity of marine life but are increasingly threatened by anthropogenic activities. To assess changes in community composition and the recovery potential of coral reefs in a changing climate, documenting sexual reproduction and understanding its environmental drivers are essential. Here, we report the exact timing and reproductive strategies for 375 individual coral colonies across 28 species from 10 genera between February 2024 and April 2025 at a near-shore reef in Baa Atoll, Maldives. We identify two peak periods of multi-specific spawning, coinciding with the monsoonal transition seasons. We note variations in spawning patterns within and between taxa, documenting the occurrence of extended breeding via asynchronous spawning of colonies within a species and split-spawning of individual colonies across lunar months and bi-annual seasons. Our results show that larger spawning events in a given month are significantly correlated with lower wind speeds, higher sea surface temperatures, and higher levels of solar insolation. These findings highlight the influence of environmental cues on the timing and extent of coral reproduction and provide the first detailed spawning records for several non-Acropora genera in the Maldives, contributing a critical baseline for future research.